(untitled) (Texas Journal of Medical Science, 2026)
This article analyzes the bidirectional biochemical relationships between diabetes mellitus and oral health based on scientific literature from the past five years. The relationship between periodontitis and diabetes mellitus has been demonstrated to occur through inflammatory processes, oxidative stress, advanced glycation end products (AGEs) and their receptors (RAGE), cytokine cascades, and oral microbiota dysbiosis. Meta-analysis results indicate that non-surgical periodontal treatment can reduce HbA1c levels by 0.4–0.6%, which has significant practical implications for diabetic patients. Furthermore, integrated approaches to managing oral health alongside diabetes mellitus are discussed.